MEMPELAJARI KESTABILAN DAN EFEK IRITASI SEDIAAN LIPSTIK YANG DIFORMULASI DENGAN LEMAK KAKAO - Alfrida Lullung Sampebarra (Jurnal Industri Hasil Perkebunan, 2016)
A study on stability and irritation effects of lipstick, formulated with cocoa butter has been done.The basic formulas of the lipstick refer to Risnawati et al, formula (2012). In this case, the addition of cocoabutter and ceraalba in the formulation of the lipstics was varied, respectively, at A (5,23% and 32,17%), B(10,40% and 26,96%), and C (15,70% and 21,74%) (w/w). The results showed that the addition of 5,23%cocoa butter and 32,17% cera alba (A), resulted in the best in the lipstick formulas, in terms of homogenity,melting point, sticking power on the lips, and color intensity. In the clinical test, it also showed not irritationefects on the skin.Keywords: lipstick, cocoa butter, stability, skin irritation